2020
DOI: 10.21577/0103-5053.20190189
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Polyketides and Macrolides from Microsphaeropsis arundinis

Abstract: The endophytic fungus Microsphaeropsis arundinis was isolated from the capitula of the tropical plant Paepalanthus planifolius (Eriocaulaceae). The fungus was cultivated in seven different media, and the ethyl acetate extracts were tested against tumor cell lines using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide MTT assay. The culture was scaled up using parboiled rice medium, and the crude extract was purified by classical chromatographic analyses, leading to the isolation of seven compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The biological activity of modiolide A, a C-4 hydroxy analogue of pyrenolide C, has been reported in the literature. It displayed the lack of cytotoxicity against HepG2 and A549 cell lines, low cytotoxicity against MCF-7, LP07, and LM3 (IC 50 61, >125, and 292 μg/mL, respectively), and very low phytotoxic activity; data on its antimicrobial activity are contradictory. , In the structures of 3 and 5a , b there is a double bond conjugated with a carboxyl group; however, they do not demonstrate antibacterial activity or toxicity to infusoria, unlike stagonolide A , and pyrenolide C (Table ). Thus, conjugation with the carbonyl, and not the carboxyl, is responsible for the nonselective toxicity of TMLs in all bioassays.…”
Section: Resultsmentioning
confidence: 99%
“…The biological activity of modiolide A, a C-4 hydroxy analogue of pyrenolide C, has been reported in the literature. It displayed the lack of cytotoxicity against HepG2 and A549 cell lines, low cytotoxicity against MCF-7, LP07, and LM3 (IC 50 61, >125, and 292 μg/mL, respectively), and very low phytotoxic activity; data on its antimicrobial activity are contradictory. , In the structures of 3 and 5a , b there is a double bond conjugated with a carboxyl group; however, they do not demonstrate antibacterial activity or toxicity to infusoria, unlike stagonolide A , and pyrenolide C (Table ). Thus, conjugation with the carbonyl, and not the carboxyl, is responsible for the nonselective toxicity of TMLs in all bioassays.…”
Section: Resultsmentioning
confidence: 99%
“…VK-13, 6,92 and Microsphaeropsis arundinis . 93 Cephalosporolide C was found in extracts obtained from cultures of closely related Cephalosporium aphidicola ACC 3490, 94 Cordyceps militaris BCC 2816, 95 and Isaria fumosorosea ACCC 37775. 96 Considering the structural revision of cephalosporolide J and bassianolone proving their identity as cephalosporolide C, this compound can be also produced by Armillaria tabescens JNB-OZ344 97 and Beauveria bassiana .…”
Section: Analysis Of Ten-membered Lactones Described For the Entire P...mentioning
confidence: 99%
“…A new metabolite, (R)-1 -(2,5-dihydroxyphenyl)-1 -oxobutan-3 -ylacetate (4), was isolated, alongside six known compounds, (R)-1-(2,5-dihydroxyphenyl)-3-hydroxybut -anone (5), 1-(2,5-dihydroxyphenyl)-2-buten-1-one ( 6), (R)-6-hydroxy-2-methyl-4-chrom -anone (7), modiolide D (84), modiolide E (85), and modiolide A (86). These compounds were obtained from the endophyte fungus M. arundinis, residing within the plant Paepalanthus plani-folius [8,23]. Additionally, Botero et al (2020) reported, for the first time, that compound 5 exhibited moderate cytotoxic activity against murine breast adenocarcinoma (LM3), with IC 50 values of 36.83 ± 4.86 µg/mL, while compound 6 displayed moderate cytotoxic activity against human breast cancer (MCF-7), with IC 50 values of 33.95 ± 3.62 µg/mL [8].…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…These compounds were obtained from the endophyte fungus M. arundinis, residing within the plant Paepalanthus plani-folius [8,23]. Additionally, Botero et al (2020) reported, for the first time, that compound 5 exhibited moderate cytotoxic activity against murine breast adenocarcinoma (LM3), with IC 50 values of 36.83 ± 4.86 µg/mL, while compound 6 displayed moderate cytotoxic activity against human breast cancer (MCF-7), with IC 50 values of 33.95 ± 3.62 µg/mL [8]. Keusgen et al (1996) successfully isolated a cerebroside, namely N-2"-hydroxy-3'Eoctadecenoyl-1-O-β-D-glucopyranosyl-9-methyl-4E,8E-sphingadiene (98), through alterations of the culture medium for the fungus M. olivacea F010 [39].…”
Section: Cytotoxic Activitymentioning
confidence: 99%